Magnetic and structural characteristics of ambient pressure fcc phase Ho and Tb thin films. (19th March 2021) - Butler, T; Buckley, R G; Granville, S
Abstract: We report the results of an investigation into the structural and magnetic properties of thin films of Ho and Tb sputtered on Ta-buffered Si substrates. As is often reported in thin films and nanoparticles of the rare earth (RE) metals, we observe both hcp and fcc phases where the relative fraction of each depends on the deposition conditions. The presence of a fcc RE phase at ambient conditions is generally claimed to be strain stabilised as in the bulk the fcc phase is only thermodynamically stable at elevated pressures. We find the lattice constants of the fcc phases in our films to coincide with values for the Ho- and Tb- hydrides, and analysis of the magnetic measurements shows that the Ho fcc phase is paramagnetic at ambient temperatures and antiferromagnetic at low temperatures, also a feature of the RE-hydrides. By considering both the structural and magnetic measurements on Ho and Tb films together, we demonstrate that the observed fcc phase is the antiferromagnetic rare earth hydride, which readily forms at the RE/Ta interface in the presence of the residual and outgassed hydrogen in vacuum chambers.